2019
DOI: 10.1007/s00420-019-01461-0
|View full text |Cite
|
Sign up to set email alerts
|

Is combining human service work with family caregiving associated with additional odds of emotional exhaustion and sickness absence? A cross-sectional study based on a Swedish cohort

Abstract: PurposeThe aim of the study is to examine to what extent human service work and family caregiving is associated with emotional exhaustion and sickness absence, and to what extent combining human service work and family caregiving is associated with additional odds. Methods Data were derived from participants in paid work from the Swedish Longitudinal Occupational Survey of Health, year 2016 (n = 11 951). Logistic regression analyses were performed and odds ratios and 95% confidence intervals estimated for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…14 According to a Swedish study, caregivers providing high-intensity care were more likely to report longterm sickness absence than non-caregivers. 13 We are aware of two other studies that have examined the association between caregiving…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 According to a Swedish study, caregivers providing high-intensity care were more likely to report longterm sickness absence than non-caregivers. 13 We are aware of two other studies that have examined the association between caregiving…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] In a Swedish study, caregiving workers were more likely to report a longterm sickness absence than non-caregiving workers. 13 Further, a study on European working adults reported that among women, family caregivers had an increased risk of a long-term sickness absence, while among men, no associations were found. 14 However, these previous studies did not analyse the risk according to diagnostic causes of the sickness absences.…”
Section: Introductionmentioning
confidence: 99%
“…Demands and resources could also potentially fall outside the work context, stemming from the home sphere. Thus, multiple hours doing unpaid work during spare time, for example housework or caregiving, may be stressful and may take its toll on individuals' mental health (Drake et al, 2019). In accordance with the social role theory, population-based figures from several European countries show that women spend far more time doing unpaid work (e.g., housework and childcare) than men, despite working full time (Moreno-Colom, 2017;Väänänen et al, 2005).This is also the situation in Sweden, where married or cohabiting women spend more time on unpaid work than men do (Statistics Sweden, 2018).…”
Section: Demands and Resources In The Home Sphere For Teachersmentioning
confidence: 99%
“…Unpaid work and caring for others can be emotionally exhausting, but leisure activities, through possibilities for recovery, can help alleviate this exhaustion. Some studies support a link between time spent on caring for children or relatives and emotional exhaustion (Bekker et al, 2005;Drake et al, 2019). However, other studies do not show these patterns (Harryson et al, 2012;.…”
Section: Home Demands and Resources And Depressive Symptoms In Teachersmentioning
confidence: 99%
See 1 more Smart Citation